Kajian Sosial, Ekonomi Dan Lingkungan Terhadap Perkembangan Wisata Delta Fishing Buduran Sidoarjo: Social, Economic and Environmental Studies on the Development of Delta Fishing Tourism Buduran Sidoarjo - Rizal, As'at; Miftahorrotmat, Agus; Indayani, Lilik (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2019)
Tourism has an influence on social, economic and environmental life for the people of the tourism area, both from positive and negative sessions, from the economic sector, there are a lot of jobs that arise starting from the provision of accommodation services, restaurants, tourism services, to souvenir businesses. This development will also have an impact on State and Regional revenues from the tax sector. Priono (2011), on the other hand, also changes in social society and the environment The purpose of this study is to determine social, economic and environmental develop- ment of tourism objects. And examine social, economic and environmental development of tourist objects This type of research survives with a qualitative approach, data collection techniques using in-depth interviews or in-depth interviews with informants including residents around the area, tourism and tourist managers and key informants include community leaders, youth organizations. Data analysis techniques used data triangulation and the Miless Hubermen method. The results of the study show that: 1) the development of Delta Fishing tourism objects from social, economic and environmental studies on the area of tourism objects in gen- eral has a positive impact. 2). Social studies have shifted more openly to migrants. 3). An economic study shows medium business opportunities and provides economic activities such as food, rice stalls, parking lots. 4). Environmental studies have a negative impact on the environment due to tourist activities close to villages and access to village roads that cause pollution and are in the rice fields.